The Right to be Forgotten in Digital Media: A Study within the Framework of the European Union and Algerian Law - OUAFI, Hadja (Journal of Human Sciences, 2025)
The right to privacy is a fundamental human right, protected by international and national legislation. It safeguards an individual’s personal space, secrets, and identity from intrusion. However, technological advancements, especially in artificial intelligence, have eroded this private sphere. As society shifts toward a predominantly digital environment, the excessive exchange of personal data emphasizes the need for digital privacy rights. This includes the right to be forgotten, enabling individuals to control the erasure of their data and limit its manipulation. Efforts at both international and national levels aim to enshrine and implement this essential right in practice.